Implementation of project-based learning social studies in independent curriculum to reduce students' social loafing - Tianti, Tri; Komalasari, Kokom; Ratmaningsih, Neiny (JIPSINDO, 2024)
This paper discusses the emergence of student social loafing in group learning. It is known that social loafing is when an individual's effort is not maximized in group work rather than independent work. Project-based learning is recommended in the independent curriculum with teaching and learning activities designed to make teachers and students actively involved. This study aims to find the effect of project-based learning in social studies learning on reducing social loafing of 7th-grade students at SMP Negeri 29 Bandung using a quantitative approach correlational method. Using probability sampling techniques, researchers used instruments or distributed questionnaires to a sample of 170 people across class VII. The data processing results from this study show a positive and significant influence between variable X project-based learning and variable Y decreasing students' social loafing with a percentage of 56.4% of the project implemented and the remaining 43.6% is influenced by other factors. The implication of this study shows that project-based learning can be one of the alternatives to reduce social loafing in the classroom.